Antiviral and Immunoenhancing Properties of 7-Thia-8-Oxoguanosine and Related Guanosine Analogues - Donald F Smee; Howard B Cottam; Brahma S Sharma; Ganesh D Kini; Ganapathi R Revankar; Emmanuel A Ojo-Amaize; Robert W Sidwell; Weldon B Jolley; Roland K Robins (Canadian Journal of Infectious Diseases)
7-thia-8-oxoguanosine (TOGuo) is the first reported structure of a family of modified guanosine analogues exhibiting antiviral activity in rodent models. Its spectrum of action includes interferon-sensitive viruses such as alphaviruses, bunyaviruses, corona viruses, flaviviruses, picornaviruses and, to a lesser extent, herpesviruses. Early treatment before or shortly after virus challenge is necessary to protect animals from mortality. The protective effect of TOGuo against Semliki Forest and Punta Toro viruses can be eliminated by co-treatment with antibody to alpha/ beta-interferon. indicating that interferon induction is of prime importance for antiviral activity against these two viruses. Immunological studies indicate that the nucleoside induces alpha-interferon and activates B cells, natural killer cells, antibody-dependent cytotoxic cells and macrophages. TOGuo also has adjuvant activity, since its use in combination with a killed Ll210 leukemia cell vaccine greatly reduced the mortality of mice inoculated with live Ll210 leukemia cells compared with the vaccine used alone. Several related guanosine analogues show similar antiviral and immunoenhancing properties, including 7-methyl-8-oxoguanosine, 7-methyl-8-thioxoguanosine and 7-deazaguanosine. These studies indicate that certain modifications at the 7 and 8 positions of guanosine may confer antiviral and immunostimulatory properties to nucleoside analogues.